Analisis kebutuhan bahan ajar berbasis kearifan lokal budidaya nanas madu belik - Erwanto Erwanto; Fenny Roshayanti; Joko Siswanto; Muhammad Saipul Hayat (Jurnal Kualita Pendidikan, 2020)
This study aims to determine the initial description of the need for teaching materials based on local wisdom of belik honey pineapple cultivation. The research method used is descriptive with a sample of 36 students of class XI MIPA 4 SMA Negeri 1 Moga, 9 teachers of Biology MGMP Pemalang, 5 farmers of belik honey pineapple. Data collection methods by observation and interviews. Observation using an online questionnaire about teacher teaching material needs and student learning material needs. Apart from that, he also conducted interviews using interview guides to pineapple farmers in Mendelem village, Belik sub-district, Pemalang district. The results of the analysis of the needs for the development of teaching materials students want the types of teaching materials that have criteria that are easy to learn, fun, interesting, various learning resources, interactive, structured, and detailed so that they can be used independently. The results of the analysis of teaching material need that the teacher wants have criteria to increase student enthusiasm for learning, creative thinking, activities, learning outcomes, development of teaching materials, easy, in the form of modules, based on local wisdom, independent. This description can be used in the development of teaching materials according to student needs. Teachers can improve the quality and quality of learning and know the types of teaching materials based on needs, namely in the form of e-modules.